The impact of firewall on TCP and UDP throughput in an openflow software defined network - Mutaz Hamed Hussien Khairi; Sharifah H. S. Ariffin; N. M. Abdul Latiff; Kamaludin Mohamad Yusof; M. K. Hassan; Mohammad Rava (Institute of Advanced Engineering and Science, 2020)
Software defined networking (SDN) is an emerging networking paradigm that provides more flexibility and adaptability in terms of network definition and control. However, SDN is a logically centralized technology. Therefor the control plane (i.e. controller) scalability in SDN in particular, is also one of the problems that needs further focus. OpenFlow is one of the protocol standards in SDN, which allow the separation of the controller from the forwarding plane. The control plane has an SDN embedded firewall and is able to enforce and monitor the network activity. This firewall can be used to control the throughput. However, it may affect SDN performance. In this paper, throughput will be used as a performance metric to evaluate and assess the firewall impact on two protocols; transmission control protocol (TCP) and user datagram protocol (UDP) that passes through the forwarding planes. The evaluations have been verified through simulating the SDN OpenFlow network using MININET. The results show that an implementation of firewall module in SDN creates a significant 36% average drop for TCP and 87% average drop for UDP in the bandwidth which eventually affect the quality of the network and applications.